Enhanced Immune Response Improves Resistance to Cadmium Stress in Triploid Crucian Carp - Liu, Wen-bin; Wang, Min-meng; Dai, Liu-ye; Dong, Sheng-hua; Yuan, Xiu-dan; Yuan, Shu-li; Tang, Yi; Liu, Jin-hui; Peng, Liang-yue; Xiao, Ya-mei (Frontiers in Physiology, 2021)
Previous research has indicated that triploid crucian carp (3n fish) had preference in the resistance to Cadmium (Cd) compared to Carassius auratas red var. (2n fish). In this article, comparative research is further conducted between the 2n and 3n fish in term of the immune response to Cd-induced stress. Exposure to 9 mg/L Cd for 96 h changes the hepatic function indexes remarkably in the 2n fish, but not in the 3n fish. In the serum of Cd-treated 2n fish, the levels of alanine amino transferase, aspartate aminotransferase, adnosine deaminase and total bilirubin are significantly increasing, while the levels of total protein, albumin, lysozyme and anti-superoxide anion radicals are decreasing demonstrating hepato toxicity. By analysis of transcriptome profiles, many immune-related pathways are founded to be involved in the response of 3n fish to the Cd-induced stress. Expression levels of the immune genes, including the interleukin genes, tumor necrosis factor super family member genes, chemokine gene, toll-like receptor gene and inflammatory marker cyclooxygenase 2 gene are significantly enhanced in the hepatopancreas of the Cd-treated 3n fish. In contrast, the expression levels of these genes are decreasing in the 2n fish. This research provides theoretical basis for polyploid fish breeding and is helpful to ecological restoration of water pollution.